Gestión pedagógica en el aula: “clima social escolar, desde la percepción de estudiantes y profesores del séptimo año de educación básica del centro educativo Ciudad de Gualaceo y Nicanor Aguilar Maldonado del cantón Gualaceo, provincia del Azuay en el año lectivo 2012-2013. - Ordoñez Ordoñez, Clara Victoria (2013)
The pedagogical gestion and the classroom environment are very important topics to a quality education. So, it is necessary to study the theorical part since the students’ perception and teachers in the seventh year of basic education in Gualaceo - San Juan, in Azuay. After a research process to carry out all the objectives applying inquiries from Moos and Trickett assigned to teachers and students. The gestion learning inquiry of the teachers was acquired in the evaluation given by the Education Ministry in 2011.Observations were carried out in the teacher classes in order to see the educational strengthens and weaknesses in the classroom. The results from the research helped us to know there is a well performance of the pedagogical gestion even though it depends of the teacher abilities, the environment and the students control by their representatives. The educational proposal tries to teach the students and their representatives in their different aspects such as, responsibility, self-control, check their tasks and values in order to optimize the academic performance.